SOSIALISASI COVID 19 PADA IBU RUMAH TANGGA (IRT) SEBAGAI UPAYA PENCEGAHAN PENULARAN COVID-19 DI DESA SELAT KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Ria Harmayani; Ni Made Andry Kartika; Bukhori Muslim; Sukran Makmun (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2020)
One of the visions and missions of national public health development is to improve the quality of human health. One way to achieve this is the implementation of the Covid-19 socialization program. The target of the Covid-19 socialization program is housewives who are given further understanding and assistance regarding Covid-19 so that they are able to independently improve the quality of their personal, family and environmental health in social life and change mindsets in maintaining health. The problem that the service team wants to solve in this service activity is the realization of increased awareness of personal and family health as well as the environment from Covid-19, namely management of maintaining health that is interrelated with the role of housewives as the spearhead of family health. Methods or implementation steps carried out in the service activities of lecturers from Nahdlatul Wathan University (UNW) Mataram, namely conducting socialization with the service team. The result of this service is the provision of Covid-19 material and management of maintaining health in service activities or programs to housewives as the target of activities. From this activity, it is able to increase passion and change in a broader mindset about the understanding of Covid-19, increase awareness of maintaining health and motivate the application of new normal adaptations and clean living habits of housewives so as to maximize the implementation of the responsibility of maintaining family health. In addition, housewives are provided with knowledge, direct practice and are involved in practicing the material that has been described.